# The most simple way to split equations, left align them and have a space between them?

I have four equations which I want to split, align and make sure there is a space between the equations.

\begin{align*}
\sum^\infty_{i=1} (3t_{2i-1}+t_{2i})9^{-i} \\
=\sum^\infty_{i=1} (3t_{2i-1}+t_{2i})3^{-2i}\\
= \sum^\infty_{i=1} 3^{-(2i-1)} t_{2i-1} + 3^{-2i} t_{2i}\\
=\sum^\infty_{i=1} t_i 3^{-i}
\end{align*}


I tried using the align environment, but it aligns to the right.

I tried using flalign but this leaves no space between the equations.

• You've missed a * at \end{align*}. Commented Jul 16, 2016 at 22:10
• Just FYI, your question doesn't really seem to be about sharelatex itself, so I added a few more appropriate tags. the fact that you may be using sharelatex to write LaTeX is not relevant, unless your question is specifically about sharelatex itself, how to use it, or some problem you're having with the service Commented Jul 16, 2016 at 22:53
• @audiophiel I took the liberty of adding it Commented Jul 16, 2016 at 22:54
• the thing you're missing is an & which is what marks the division between the left-hand side of an equation and the right-hand side. you need to read some elementary documentation. try texdoc amsmath, for example. Commented Jul 17, 2016 at 1:34
• @Au101 how do you make edits with just one letter? is that a matter of reputation? Commented Jul 17, 2016 at 6:22

Something like

\documentclass[preview]{standalone}
\usepackage{amsmath}
\begin{document}
\begin{align*}
&\sum^\infty_{i=1} (3t_{2i-1}+t_{2i})9^{-i}&& \\
&=\sum^\infty_{i=1} (3t_{2i-1}+t_{2i})3^{-2i}\\
&= \sum^\infty_{i=1} 3^{-(2i-1)} t_{2i-1} + 3^{-2i} t_{2i}\\
&=\sum^\infty_{i=1} t_i 3^{-i}
\end{align*}
\end{document}


should do what you want:

You can play arround with the & signs a bit to get exactly what you want.

I'm not sure what you mean by not leaving space between the equations, but flalign works fine; see below. Image at the top is flalign*, at the bottom it's align*.

\documentclass[preview]{standalone}
\usepackage{amsmath}
\begin{document}
\begin{flalign*}
&\sum^\infty_{i=1} (3t_{2i-1}+t_{2i})9^{-i}&\\
&=\sum^\infty_{i=1} (3t_{2i-1}+t_{2i})3^{-2i}&\\
&= \sum^\infty_{i=1} 3^{-(2i-1)} t_{2i-1} + 3^{-2i} t_{2i}&\\
&=\sum^\infty_{i=1} t_i 3^{-i}
\end{flalign*}
\begin{align*}
&\sum^\infty_{i=1} (3t_{2i-1}+t_{2i})9^{-i}\\
&=\sum^\infty_{i=1} (3t_{2i-1}+t_{2i})3^{-2i}\\
&= \sum^\infty_{i=1} 3^{-(2i-1)} t_{2i-1} + 3^{-2i} t_{2i}\\
&=\sum^\infty_{i=1} t_i 3^{-i}
\end{align*}
\end{document}